Security for business and industry - Hemphill, Charles F. (Homewood, Ill. : Dow Jones-Irwin, 1971)
This book deals with business losses- why they occur, and how they may be avoided- from a security standpoint. It was written to show every individual in a management or administrative position how to retain hard-earned profits.
Includes index.
Includes bibliographical references: p. 301-305.
hza 26/07/2018
Loans
Keywords: Industries